Antibacterial and Cytotoxic Activities of the Leaf Extract of Holigarna longifolia Roxb. - Ekram, AE; Hoque, KMF (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Dhaka Univ. J. Pharm. Sci. 12(1): 83-85, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16305